Caracterização de cinza do bagaço de cana-de-açúcar para emprego como pozolana em materiais cimentícios - Cordeiro,Guilherme Chagas (2009)
This work presents the results of morphological and physical-chemical characteristics of a sugar cane bagasse ash material sample produced under controlled burning conditions. The investigation was carried out by analyzing chemical composition, X-ray diffraction, 29Si nuclear magnetic resonance, morphology, thermal analysis, particle size, specific surface, and density. Moreover, the pozzolanic activity of the ash was evaluated by pozzolanic activity index and Chapelle's method. The results suggest that the sugar cane bagasse ash has adequate properties to be used as pozzolan in construction materials.